Mineralisation from hot fluid flows in the sandstone-type uranium deposit in the Kailu Basin, Northeast China. Issue 1 (2nd January 2018) - Nie, Fengjun; Yan, Zhaobin; Xia, Fei; Li, Mangen; Feng, Zhibing; Lu, Yayun; Cai, Jianfang
ABSTRACT: The Qianjiadian-Baixingtu uranium deposit (QBUD) is in the post-Jurassic extensional Kailu basin of northeast China. There is a well-developed fault system in and adjacent to the deposit, and uranium mineralisation appears controlled by faults F 1, F 2, and F 3. Lots of diabase (dolerite) intrusions related to regional faults are extensive throughout the QBUD. The ellipsoidal and lenticular mineralised bodies in the QBUD conflict with the interlayered oxidation genesis. Furthermore, heat from the diabase intrusions not only makes the wall rocks hard, but plenty of new cement minerals are precipitated from hot fluid flow (HFF). The clastic grains in the host sandstone are strongly altered by HFF. Carbonate cements involves calcite, ankerite, and Fe-rich dolomite. There are three inclusion temperature peaks: ∼90°C, 110-120°C, and 140-150°C, and three ranges of inclusion salinity: 5.0-10.0 wt-% NaCl equivalent, 10.1-15.0 wt-% NaCl equivalent, and 15.1-20.07 wt-% NaCl equivalent.